Defect and impurity effects in exchange bias systems - Vallejo-Fernandez, Gonzalo; Kaeswurm, Barbara; O'Grady, Kevin (Journal of Applied Physics, 2011)
We use a strong domain wall pinning model to interpret previous results on the effects of dopants and defects in the loop shift H(ex) of exchange bias systems. The effects of defects and dopants leads to a peak in the value of H(ex) as a function of the concentration, which was interpreted on the basis of the domain state model. We consider a strong domain wall pinning model such that the strength of the pins can lead to the formation of quasi-single domain grains. These single domain grains then behave as Stoner-Wohlfarth entities subject to thermal activation. This model provides excellent agreement with reported experimental data predicting the peak with concentration and the correct form of the variation in the peak shape with temperature. (c) 2011 American Institute of Physics. [doi: 10.1063/1.3556926]